The Effectiveness of TOEFL Preparation Course to Improve Students’ Reading Comprehension - Sartika Putri Sailuddin (EDU Journal - English Department of UMMU Journal, 2022)
Abstract: The purpose of this study was to measure the effectiveness of applying TOEFL Preparation in order to increase TOEFL test scores for students especially on reading section. The research to be carried out is an experimental research with a t-test sample. Participants consisted of 30 selected university students who had participated on the TOEFL preparation program under three stages, namely pretest, treatment (reading lesson), and posttest. This research method ised 2 types of instruments, namely the pretest which was used to measure students’ initial reading scores of the TOEFL test, and the posttest which was used to measure the final score results after the treatment. The data collected from both the pretest and posttest were then analyzed using the paired-sample t-test in IBM SPSS 25. it was found that there was a significant difference in the scores for pre-test (M=42.4, SD=6.3) and post-test (M=47.3, SD=6.7) conditions; t(41)=-9.37, p<.001 and the effect size d=-1.2. This results showed that Ha is accepted an H0 is rejected; therefore TOEFL preparation course is effective to improve students’ reading comprehension scores. The effectiveness of this program is strongly supported by the learning model applied, namely PBL. The application of PBL in this program is very suitable because students are guided to identify problems that usually arise in TOEFL questions and how to solve them.